2019
DOI: 10.20517/2574-1225.2019.22
|View full text |Cite
|
Sign up to set email alerts
|

One anastomosis gastric bypass and esojejunostomy in rats: surgical techniques

Abstract: One anastomosis gastric bypass (OAGB) is a popular bariatric procedure, but controversies remain regarding biliary reflux and the potential risk of cancer. Esophagojejunostomy (EJ) in rats is a validated and reproducible model for the development of metaplasia [Barett's esophagus (BE)] and esophageal adenocarcinoma (EA) with a minimal exposure of 12 to 20 weeks. We are analyzing the risks of BE and EA in an OAGB rat model and comparing these with the EJ rat model. The purpose of this study is to describe our O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, other procedures such as the one anastomosis gastric bypass (OAGB) have been growing in popularity despite the concern for bile reflux. The Paris Descartes Faculty of Medicine studied reflux, Barrett's esophagus, and esophageal cancer [6] . They shared their findings and concluded that the OAGB operation appears to be safe in an animal model.…”
mentioning
confidence: 99%
“…However, other procedures such as the one anastomosis gastric bypass (OAGB) have been growing in popularity despite the concern for bile reflux. The Paris Descartes Faculty of Medicine studied reflux, Barrett's esophagus, and esophageal cancer [6] . They shared their findings and concluded that the OAGB operation appears to be safe in an animal model.…”
mentioning
confidence: 99%